USING THE JIGSAW TECHNIQUE TO IMPROVE STUDENT READING COMPREHENSION - Fadhlan Saini; Nur Halimah; Indah Wardaty Saud; Rara Ayu Ningsi Paputungan (Universitas Muhammadiyah Gorontalo, 2020)
This research aims to improve students’ reading comprehension in the narrative text by using jigsaw technique. The subject of this research was the eleventh grade of social class students at SMA Negeri 1 Modayag in academic year 2019-2020. This research of this study was conducted by using Classroom Action Research (CAR). The data used in this study was pre-test result, post-test, and observation sheet. This research wa conducted in two cycles, each consisted of planning, action, observation, and reflection. The data were collected through qualitative and quantitative data. Qualitative data were data obtained by analyzing observations. Then, quantitative data were obtained from students’ pre-test and post-test scores. The result of this study indicated that there was an increase in students in reading narrative texts. The average of the pre-test was 48%. The mean of the first cycle was 58%, it showed that the scores and the mean in the first cycle were better that pre-test. The percentage of students and the mean in the first cycle were better than pre-test. The percentage of students with 75 or more points increases. In the post-test of cycle 1, 14 students passed or got score up to 75. In the post-test of cycle 2, students who got 75 points or more were 22 (100%) and an increase was about 88%. In other words, students’ reading comprehension in narrative texts increases. Keywords: reading comprehension, narrative text, jigsaw technique